2020
DOI: 10.1590/0001-3765202020191107
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-apoptotic effects of selenium nanoparticles against murine eimeriosis

Abstract: Eimeriosis is caused by a protozoan parasite of the genus Eimeria and infection affecting most domestic animal species. The aim of this research was to comprehend the impact of selenium nanoparticles (SeNPs) on eimeriosis induced by Eimeria papillata in mouse jejunum, and how they work as antioxidants and antiapoptotic agents against eimeriosis. The numbers of meronts, gamonts, and developing oocysts of E. papillata reduced after the infected mice were treated with the SeNPs. The levels of malondialdehyde (MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…The FTIR spectrum, which represented symmetric and asymmetric vibration bands of the SeNPs, showed a broad peak at 3200-3500 cm -1 , indicating the presence of the amide (-NH) group, while a strong peak at 1637 cm -1 corresponded to the C=O group. 23 The peak at 767.5 cm -1 was related to the stretching mode of the metal peaks of Se ( Figure 1C).…”
Section: Characterization and Cellular Uptake Of Senpsmentioning
confidence: 98%
“…The FTIR spectrum, which represented symmetric and asymmetric vibration bands of the SeNPs, showed a broad peak at 3200-3500 cm -1 , indicating the presence of the amide (-NH) group, while a strong peak at 1637 cm -1 corresponded to the C=O group. 23 The peak at 767.5 cm -1 was related to the stretching mode of the metal peaks of Se ( Figure 1C).…”
Section: Characterization and Cellular Uptake Of Senpsmentioning
confidence: 98%
“…Se NPs are found to be more effective than sodium selenite with regard to their anti-coccidial, anti-oxidant, anti-apoptotic and anti-inflammatory role against Eimeria parasite in the jejunum of mice (Alkhudhayri et al, 2018;Alkhudhayri et al, 2020). Furthermore, Dkhil et al demonstrated the protective roles of Se NPs in mice infected with Schistosoma mansoni, indicating that Se NPs could possess therapeutic anti-schistosomal activity in the treatment of intestinal schistosomiasis (Dkhil et al, 2019).…”
Section: Anti-parasite Effects Of Selenium Nanoparticlesmentioning
confidence: 99%
“…Recently, specific forms of nanomaterials have been produced including metals such as silver, gold, copper, zinc and magnesium, creating various degrees of antimicrobial activity ( Hussein et al, 2018 ). Moreover, Alkhudhayri et al (2020) reported the antioxidant and the antiparasitic effect of nanoselenium.…”
Section: Introductionmentioning
confidence: 99%